Two distinct CXC chemokine receptors (CXCR3 and CXCR4) from the big-belly seahorse Hippocampus abdominalis: Molecular perspectives and immune defensive role upon pathogenic stress. Issue 65 (June 2017) - Priyathilaka, Thanthrige Thiunuwan; Oh, Minyoung; Bathige, S.D.N.K.; De Zoysa, Mahanama; Lee, Jehee
Abstract: CXC chemokine receptor 3 (CXCR3) and 4 (CXCR4) are members of the seven transmembrane G protein coupled receptor family, involved in pivotal physiological functions. In this study, seahorse CXCR3 and CXCR4 (designated as HaCXCR3 and HaCXCR4 ) cDNA sequences were identified from the transcriptome library and subsequently molecularly characterized. HaCXCR3 and HaCXCR4 encoded 363 and 373 amino acid long polypeptides, respectively. The HaCXCR3 and HaCXCR4 deduced proteins have typical structural features of chemokine receptors, including seven transmembrane domains and a G protein coupled receptors family 1 profile with characteristic DRY motifs. Amino acid sequence comparison and phylogenetic analysis of these two CXC chemokine receptors revealed a close relationship to their corresponding teleost counterparts. Quantitative real time PCR analysis revealed that HaCXCR3 and HaCXCR4 were ubiquitously expressed in all the tested tissues, with highest expression levels in blood cells. The seahorse blood cells and kidney HaCXCR3 and HaCXCR4 mRNA expressions were differently modulated when challenged with Edwardsiella tarda, Streptococcus iniae, lipopolysaccharide, and polyinosinic:polycytidylic acid, confirming their involvement in post immune responses. Highlights: Full length coding sequences of CXC chemokine receptor 3 and 4 from Seahorse (HaCXCR3 and HaCXCR4) were identified. The HaCXCR3 and HaCXCR4 deduced proteins have typical structural features of chemokine receptors. The HaCXCR3 and HaCXCR4 mRNA was significantly up-regulated upon live pathogens and PAMPs in blood and kidney.